Pengaruh Struktur Modal Terhadap Nilai Perusahaan Dengan Kinerja Perusahaan Sebagai Variabel Intervening (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2017-2019) - Iin Cahyaningsih; Ronny Malavia Mardani; Ety Saraswati (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThis study aims to determine how the effect of the capital structure proxied using DER, DAR, and EAR on firm value with firm performance as an intervening variable. This research uses quantitative research and purposive sampling method is chosen in selecting the sample. All manufacturing companies listed on the Indonesia Stock Exchange (IDX) were sampled in this study, during the 2017-2019 research period. The results of the analysis in this study that there is a significant positive effect of capital structure on firm value. There is a significant positive effect of capital structure on company performance. The results of the analysis using the intervening variable are that there is an indirect effect between capital structure on firm value and firm performance as an intervening variable. Keywords: Capital Structure, Firm Value, and Firm Performance.